IMPORTANCE PERFORMANCE ANALYSIS WILAYAH KERJA BALAI PENYULUHAN PERTANIAN DESA KUALA DUA KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Hery Medianto Kurniawan (Jurnal Ekonomi STIEP, 2022)
This study was to determine the quality of services provided by WKPP Kuala Dua Village Sungai Raya District Kubu Raya Regency to Farmer Groups. This research was conducted at WKPP Kuala Dua Village, Sungai Raya District. The research time was carried out for 2 (two) months, namely April - May 2022. The research variables included tangible, realiability, responsiveness, assurance and empathy. Data analysis using Importance and Performance Analysis method. The results showed that the statement was dissatisfied with the service quality of WKPP Desa Kuala Dua, where performance was smaller than importance, namely the average value of interest was 4.54 and the average value of performance was 4.29. Based on the Cartesian Diagram, it can be concluded: First Quadrant (A), includes attributes: The appearance of PPL WKPP Kuala Dua Village neatly affects the services provided, WKPP reliability in conveying agricultural information to farmers from beginning to end is very important and understanding of PPL officers towards farmers is very important . Quadrant Two (B), which includes attributes: The reliability of WKPP in conveying agricultural information to farmers from beginning to end is very important, Clarity of information conveyed by WKPP to farmers is very important, Clarity of information conveyed by WKPP to farmers is very important, Ability of PPL in carrying out work related to farmers is very important, feeling safe and comfortable for farmers dealing with PPL officers is very important, WKPP's seriousness towards the interests of farmers in farming is very important, flexibility of PPL services to farmers is very important. Third Quadrant (C), which includes attributes: Clean and comfortable condition of the WKPP Village Kuala Dua building is very important, Timeliness of WKPP in service according to the promise given is very important, Accuracy of WKPP in document administration is very important, Time provided by the WKPP PPL in responding to farmers' requests quickly is very important. Fourth quadrant (D), which includes attributes: The state of up-to-date equipment owned by WKPP Desa Kuala Dua is very important, The condition of human resources owned by WKPP Desa Kuala Dua is very important, WKPP's serious attention to farmers who have problems is very important, Willingness of PPL in helping farmers' difficulties is very important, PPL's ​​patience in serving farmers is very important. The support of WKPP Desa Kuala Dua to PPL officers to carry out their duties properly is very important. PPL's ​​individual attention to farmers when facing problems is very important. PPL's ​​understanding of farmers' needs is very important. Keywords: Importance, Performance, Farmer Group, WKPP, Kuala Dua Village